Assessing Nutritional Knowledge and Physical Health Among Football Players: A Pilot Study from Three Sports Clubs in Western Romania - Gabriel Roberto Marconi; Brigitte Osser; Gyongyi Osser; Caius Calin Miuța; Csongor Toth; Viorel Petru Ardelean; Anca Dicu; Corina Dalia Toderescu; Laura Ioana Bondar (Sports)
Background: Football players require optimal nutrition and physical fitness to enhance their performance and maintain their health. Understanding the relationships among nutritional knowledge, dietary habits, physical health, and substance use in athletes is essential for developing effective strategies. This study investigates these factors in male football players aged 16–33 years. Methods: The study involved 60 male football players from three teams in Liga4Arad. A mixed-methods approach was used, incorporating a self-developed pilot questionnaire and internationally validated instruments. The reliability of the questionnaire was confirmed using Guttman’s λ2. The questionnaire assessed nutritional knowledge, eating habits, substance use, and physical health parameters, including body fat percentage and training frequency. Spearman’s correlation was used to analyze the data and explore the interrelationships between these factors. It is important to note that the pilot questionnaire used in this study was self-developed and not previously validated in this specific context. Results: Nutritional knowledge was positively correlated with healthier eating habits (ρ = 0.675, p < 0.001). Intensive training and higher physical activity levels were both associated with improved body composition and lower body fat (ρ = 0.341, p = 0.006). Supplement use was moderately correlated with alcohol consumption (ρ = 0.548, p < 0.001) and weakly correlated with smoking (ρ = 0.348, p = 0.007). Conclusions: The study highlights a strong relationship between nutritional knowledge and healthier eating habits among football players, as well as the significant role of frequent intense training in reducing body fat percentages and enhancing physical fitness. Additionally, the findings suggest a moderate association between dietary supplement use and alcohol consumption, underscoring the need for tailored interventions to address substance use and its impact on players’ health behaviors and performance.